Pengaruh Kualitas Produk, dan Kualitas Pelayanan Terhadap Minat Beli Ulang Pada UD. TAUPIK di Mataram - Nazla Rizka Hidayah; Rusminah (Postgraduate, University of Mataram, 2025)
This study aims to determine the effect of product quality and the effect of service quality on repurchase interest at UD. TAUPIK in Mataram. This type of research is quantitative associative with data collection methods, namely survey samples using questionnaires via google form as a research instrument with a total sample of 100 respondents. The analysis method uses multiple linear regression analysis using the Statistical Package For The Social Sciences (SPSS) tool. The results of the study indicate that, variable (1) Product Quality has a positive and significant effect on Repurchase Interest at UD. TAUPIK with a t value for the product quality variable of 6.005> 1.98472. (2) Service Quality has a positive and significant effect on Repurchase Interest at UD. TAUPIK with a t value for the Service Quality variable of 5.809> 1.98472. The instrument test results state that the data in this study are proven to be valid and reliable and the classical assumption test states that the data is normally distributed and not multicollinearity.